2020
DOI: 10.51703/bm.v2i0.30
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Effect of Restaurant Image on the Relationship between Service & Food Quality and Customer Satisfaction

Abstract: The purpose of this study is to examine the mediation effect of restaurant image on the relationship between service qualities, food quality and customer satisfaction in restaurant industry. Questionnaire used to collect data, while Smart PLS 3.0 was used to test the hypotheses. The result of this research revealed positive and significant relationships between food quality, service quality, restaurant image and customer satisfaction. The other hand, there is no mediation effect of restaurant image in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…To fully capitalize on the bene ts of customer feedback, it is crucial for businesses to provide relevant training to their staff. Previous studies have indicated that staff training is indispensable in the café and restaurant industry, offering a range of bene ts from improved service quality and customer satisfaction [1][2][3][4] to increased e ciency [5,6] and innovation [7,8]. Speci cally, in today's rapidly changing world, people's thoughts and preferences evolve swiftly, making the ability to adapt quickly to these changes crucial.…”
Section: Introductionmentioning
confidence: 99%
“…To fully capitalize on the bene ts of customer feedback, it is crucial for businesses to provide relevant training to their staff. Previous studies have indicated that staff training is indispensable in the café and restaurant industry, offering a range of bene ts from improved service quality and customer satisfaction [1][2][3][4] to increased e ciency [5,6] and innovation [7,8]. Speci cally, in today's rapidly changing world, people's thoughts and preferences evolve swiftly, making the ability to adapt quickly to these changes crucial.…”
Section: Introductionmentioning
confidence: 99%